Improving Students' Reading Comprehension through Student Team Achievement Division Technique - N. Erna Marlia Susfenti (Loquen, 2017)
This research was aimed at investigating the process of improving students’ reading comprehension through Student Team Achievement Division Technique and examining the effect of its implementation toward students’ abilities in reading comprehension. This research was designed in 2 cycles at SMK Prawira Pandeglang Banten in the second semester of 2016/2017 academic year. The focus of this research was the improvement of students’ English reading comprehension, whereas the sub-focus was the process of improving students’ abilities in reading comprehension through the Implementation of Student Team Achievement Division Technique. The data was collected from observations and interviews. The students’ reading comprehension was assessed with multiple choices reading test. The research findings have shown that the implementation of Student Team Achievement Division Technique had improved students’ abilities in comprehend the text from 54.2% in the first cycle become 76.25% in the second cycle. Based on the results, it can be concluded that student team achievement division technique can improve reading comprehension of the students of class X SMK Prawira Pandenglang Banten.